Flexural Properties of ECC-Concrete Composite Beam - Yanhua Guan; Huaqiang Yuan; Zhi Ge; Yongjie Huang; Shuai Li; Renjuan Sun (Advances in Civil Engineering)
Rebar corrosion-induced durability issue is a major concern for bridges. The ECC cover was employed to prevent the intrusion of the corrosive agent. This paper studied the flexural behavior of ECC-concrete composite beam. The effects of bonding at the interface and fiber mesh reinforcement on the flexural properties and cracking pattern were investigated. The strain distribution and midspan deflection were evaluated. Test results show that the bonded composite beam had a higher loading capacity. But the unbonded composite beam showed better postcrack energy absorption capacity with higher midspan deflection. The fiber mesh reinforcement could further improve the flexural properties regardless of the bonding condition. The strain at the bottom of the unbonded beam was much smaller than that of the bonded beam. The penetrated cracks were observed at the ECC layer of the bonded composited beam.